The Creative Brain Under Stress: Considerations for Performance in Extreme Environments - Vartanian, Oshin; Saint, Sidney Ann; Herz, Nicole; Suedfeld, Peter (Frontiers in Psychology, 2020)
Over the last two decades, we have begun to gain traction on the neural systems that support creative cognition. Specifically, a converging body of evidence from various domains has demonstrated that creativity arises from the interaction of two large-scale systems in the brain: Whereas the default network (DN) is involved in internally-oriented generation of novel concepts, the executive control network (ECN) exerts top-down control over that generative process to select task-appropriate output. In addition, the salience network (SN) regulates switching between those networks in the course of creative cognition. In contrast, we know much less about the workings of these large-scale systems in support of creativity under extreme conditions, although that is beginning to change. Specifically, there is growing evidence from systems neuroscience to demonstrate that the functioning and connectivity of DN, ECN and SN are influenced by stress—findings that can be used to improve our understanding of the behavioural effects of stress on creativity. Toward that end, we review findings from the neuroscience of creativity, behavioural research on the impact of stress on creativity, and the systems-level view of the brain under stress to suggest ways in which creativity might be affected under extreme conditions. Although our focus is largely on acute stress, we also touch on the possible impact of chronic stress on creative cognition.